ANALYSIS OF FACTORS AFFECTING BORROWERS' INTEREST IN USING KREDIVO FINTECH PEER-TO-PEER LENDING SERVICES DURING THE COVID-19 PANDEMIC IN DENPASAR CITY - Ida Ayu Gede Yuniari Santhika Putri; Ni Made Estiyanti; Linda Yupita (LPPM STMIK Pringsewu, 2023)
This study aims to determine the factors that influence people's interest in Kota Denpasar using Kredivo peer-to-peer lending during the CO-19 pandemic. The research uses the Technology Acceptance Model (TAM) model by adding two additional variables. This study uses the convenience sampling technique as a sampling method. The number of samples in this study was 120. The basis for taking a sample of 120 people is based on Ferdinand's (2014) theory that in the SEM method, the required number of samples is at least five times the number of indicator variables. To manage data that has been obtained in the field, researchers use Partial Least Squares (PLS) and smartPLS 3.0 software. The results obtained indicate that the eight hypotheses tested have a significant relationship and can be accepted.